2003
DOI: 10.1111/j.1744-618x.2003.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Care Activities of Nurses Using Nursing Interventions Classification (NIC) Labels

Abstract: and Mary Ann McPartlan Bajo, RN PURPOSE. To describe the spiritual care activities of nurses as subsequently identified in the Nursing Interventions Classification (NIC) labels. METHODS. Data were takenfrom a larger study that used a multiple triangulation research design to describe spiritual perspectives, in tervenfions, and attitudes of 1,000 Sigma Theta Tau International members . Data analysis included desc r ip t ive and multivariate statistics for quantitative items, and content analysis for responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…In a study, the spiritual well-being and age were reported to have a significant relationship (P<0.04) (19). Similarly, the effect of age on spiritual wellbeing has been suggested in other studies (22,23). This discrepancy between or results and those of the aforementioned studies can be ascribed to the family culture and living environment of the students, who constituted the research population.…”
Section: Discussionmentioning
confidence: 86%
“…In a study, the spiritual well-being and age were reported to have a significant relationship (P<0.04) (19). Similarly, the effect of age on spiritual wellbeing has been suggested in other studies (22,23). This discrepancy between or results and those of the aforementioned studies can be ascribed to the family culture and living environment of the students, who constituted the research population.…”
Section: Discussionmentioning
confidence: 86%
“…In keeping with a focus on individual differences, there is also an emphasis on patient enablement, empowerment, and, to the greatest extent possible, self‐care (Cavendish et al., 2003; Clayton et al., 1991; Kanitsaki, 1993; Wilson, 1986). It is notable that both a respect for individual differences and patient empowerment allow for flexibility and, when necessary, variation in the enactment of presence and caring (Fuller, 1991; Mohnkern, 1992; Turkel, 2001; Yam & Rossiter, 2000).…”
mentioning
confidence: 99%
“…Results of other studies have shown four areas of spirituality that normally evaluated in patients as follows: fear of medical practices, sources of patients' internal power, feeling of hopefulness, religious practices related to the surgery, but integrity, as a dimension of spiritual evaluation, has been less reported by nurses [50]. Although the goal of nursing care, is to promote health, prevent of diseases, maintain health, and relieve patients' pain and suffering, and the spiritual care is influential in reaching these goals [51] by reducing patients' stresses during their hospitalization through focusing on optimism and hope to the mercy of God, but there are still few nurses providing spiritual care [5]. Over 50% of nurses do not try to provide spiritual care to patients in practice and feel that, they are not competent enough in this regard [46].…”
Section: Discussionmentioning
confidence: 99%
“…The professional performance of nursing is based on its theoretical knowledge, through nursing care models, which is influenced by the philosophical perspective of theorists, who define how to take care of clients and patients [3,4]. The effect of philosophy (ontology), on people's culture and lifestyle, mood, behaviors, health habits, meaning of events, perception of health and sickness, selecting treatment and care models is different in every culture and society [5][6][7], that represents: people of every society, have their own spiritual responses to stress or diseases, based on their philosophical attitudes toward the world [8]. Reaction to disease varies from person to person, such as: an unfair event from God that causes dissatisfaction with fate, a challenge that has a solution, a factor for future anxiety or sadness of losing health, the reason for creating a sense of revenge from the cause of disease with frustration, or vice versa: time for rest and care with the hope to spend the course of disease, easily [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation